Design and experimental study of a precision fluid hill-drop planter for maize - Zhengwei Zhang; Lang Zhou; Anping Ji; Zhaoran Sun; Guangyao Zhu; Xiong Chen; Junhao Pi; Chenxi Yang; Haoxuan Chen; Zhenyu Yang; Hu Tian (PLoS ONE, 2025)
The study presents the design of a precision maize hill-drop dibbler based on fluid control and zero-speed seeding theory, developed to overcome challenges of poor planting precision, seed damage, limited terrain adaptability, and low water-use efficiency in maize cultivation across the hilly regions of Southwest China. To this end, a novel precision fluid hill-drop planter was designed, integrating fluid control with zero-speed seeding theory. The device employs a seed-liquid separation and terminal mixing design, where a crank-connecting rod-driven piston pump ensures precise fluid delivery. A direct comparative experimental framework was established, evaluating the proposed planter against a traditional spoon-wheel seeder under identical bench-test conditions. Performance was assessed through CFD-DEM coupled simulation and systematic experiments across multiple dimensions: seeding precision (qualified, multiple, and miss index), hill-forming characteristics, and fluid performance (water application per hill, seed bounce distance). The comparative results demonstrated that within an operating speed range of 1.2 ~ 1.6 m/s, the new planter achieved a qualified index exceeding 91%, a significant improvement of 12.5% over the conventional device. The seed bounce distance was controlled within 5.4 mm, representing a 63.2% reduction. Furthermore, the system exhibited excellent operational stability, with a coefficient of variation for water application per hill of less than 2% and a check valve leakage rate below 3%. Through collaborative parameter optimization, breakthrough indicators were achieved: a 94.8% seed-water coincidence rate and a hill spacing deviation of no more than 1.0%. This research validates the proposed planter’s superior performance and reliability, providing an effective technical solution to enhance sowing uniformity and water-use efficiency in complex terrain.